PSYCHOANALYSIS OF RANDOLPH “RANN” COLFAX’S PERSONALITY IN PEARL S. BUCK NOVEL “THE ETERNAL WONDER” - Fajrin, Naufal; Weda, Sukardi; Iskandar, Iskandar (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2024)
In this study, the researcher analyzed the personality of the main character in a literary work. The researcher examined two issues, namely: (1) What are the personality structures of Randolph "Rann" Colfax in the novel The Eternal Wonder, (2) How is the dynamics of Randolph "Rann" Colfax's personality in the novel The Eternal Wonder. The Eternal Wonder is a novel by Pearl S. Buck. The method used in this study is qualitative descriptive method and Psychoanalytic approach. Based on the findings, there are 7 structures of Id personality found in the main character Randolph "Rann" Colfax, 7 structures of Ego personality found in the main character Randolph "Rann" Colfax, and 7 structures of Superego personality found in the main character Randolph "Rann" Colfax. Meanwhile, the analysis conducted based on the personality structures found within Randolph "Rann" Colfax revealed personality dynamics in the form of indications of positive instincts and anxiety. Keywords: Psychoanalysis, personality, impulse